Association of TGF-β2 levels in breast milk with severity of breast biopsy diagnosis - Yang, Hannah P. (Cancer Causes Control, 2015)
PURPOSE: TGF-β plays a dual role in breast carcinogenesis, acting at early stages as tumor-suppressors and later as tumor-promoters. TGF-β isoforms are expressed in breast tissues and secreted in milk, suggesting that analysis of levels in milk might be informative for breast cancer risk. Accordingly, we assessed TGF-β2 levels in milk from women who had undergone a breast biopsy and related the concentrations to diagnosis. METHODS: Milk donated by women who had undergone or were scheduled for a breast biopsy was shipped on ice for processing and testing. Breast cancer risk factors were obtained through a self-administered questionnaire and biopsy diagnoses were extracted from pathology reports. TGF-β2 levels in milk, assessed as absolute levels and in relation to total protein, were analyzed in bilateral samples donated by 182 women. Linear regression was used to estimate relationships of log transformed TGF-β2 levels and TGF-β2:total protein ratios to biopsy category. RESULTS: Milk TGF-β2 levels from biopsied and non-biopsied breasts within women were highly correlated (r(2)=0.77). Higher mean TGF-β2 milk levels (based on average of bilateral samples) were marginally associated with more severe breast pathological diagnosis, after adjusting for duration of nursing current child (adjusted p-trend=0.07). CONCLUSIONS: Our exploratory analysis suggests a borderline significant association between higher mean TGF-β2 levels in breast milk and more severe pathologic diagnoses. Further analysis of TGF-β signaling in milk may increase understanding of post-partum re-modeling and advance efforts to analyze milk as a means of assessing risk of breast pathology.